2020
DOI: 10.1007/s42398-020-00123-z
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of SARS-CoV-2 in South Asian countries: molecular evolutionary model based phylogenetic and mutation analysis

Abstract: The ongoing coronavirus disease 19 (COVID-19) pandemic has caused a very high number of infections and deaths around the globe. The absence of vaccine/drugs to counter COVID-19 has scrambled scientific communities to repurpose available medicines/vaccines. As the virus is known to mutate, using the whole genome sequences, the transmission dynamics and molecular evolutionary models were evaluated for South Asian countries to determine the evolutionary rate of severe acute respiratory syndrome coronavirus 2 (SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…It becomes very important to study the antigenic and molecular variations in the pathogenic microbial strains, particularly for RNA viruses such as SARS-CoV-2 which can mutate and create a problem for the development of vaccines and other treatment options (Abdullahi et al 2020). Maurya et al (2020) observed that mutations in SARS-CoV-2 can pose a challenge for development of vaccines that can target the diverse mutants of the virus, making continuous tracking very important. Islam et al (2020) have reported that there are higher mutations in SARS-CoV-2 genomes and disease severity in the temperate regions in comparison to other parts of the world, suggesting some sort of relationship between meteorological factors and genetic variations in the novel coronavirus.…”
Section: Recommendations For Mitigating Pandemics In the Futurementioning
confidence: 99%
“…It becomes very important to study the antigenic and molecular variations in the pathogenic microbial strains, particularly for RNA viruses such as SARS-CoV-2 which can mutate and create a problem for the development of vaccines and other treatment options (Abdullahi et al 2020). Maurya et al (2020) observed that mutations in SARS-CoV-2 can pose a challenge for development of vaccines that can target the diverse mutants of the virus, making continuous tracking very important. Islam et al (2020) have reported that there are higher mutations in SARS-CoV-2 genomes and disease severity in the temperate regions in comparison to other parts of the world, suggesting some sort of relationship between meteorological factors and genetic variations in the novel coronavirus.…”
Section: Recommendations For Mitigating Pandemics In the Futurementioning
confidence: 99%
“…It has been observed that the lethality in temperate countries is more as compared to tropical countries due to presence of few unique mutations in SARS-CoV-2 genes (Islam et al 2020 ). Mutations in virulence genes of SARS-CoV-2 was observed in several countries of Europe, Asia and Middle-East, yet the loss of human lives due to COVID-19 has been relatively lower particularly in Asia and Middle-East as compared to Europe (Islam et al 2020 ; Maurya et al, 2020 ). Therefore, the significance of weather variables is important for the occurrence and spread of COVID-19 and its rate of lethality.…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV2 genome has a high rate of recombination and adaptive expression strategies which allows them to pass into and infect several hosts through variety of environmental niches. Several studies have shown viral variations at different geographical locations like Southeast Asian (Maurya et al, 2021), European (Hryhorowicz et al, 2021) and North American nations (Attwood et al, 2022), and globally (Said et al, 2021).…”
Section: Introductionmentioning
confidence: 99%